Translation and validation into Brazilian Portuguese of the Spastic Paraplegia Rating Scale (SPRS) - Servelhere, Katiane R.; Faber, Ingrid; Coan, Ana Carolina; França, Marcondes, Junior (Arquivos de Neuro-Psiquiatria, 2016)
Hereditary spastic paraplegias (HSP) are characterized by progressive lower limb weakness and spasticity. There are no validated instruments to quantify disease severity in Portuguese. Objective To translate and validate the Spastic Paraplegia Rating Scale (SPRS) into Brazilian-Portuguese.Method Two experienced and English-fluent neurologists translated SPRS into Portuguese, creating SPRS-BR. We then assessed inter and intra-rater reliability of this version using coefficients of correlation and variability in a cohort of 30 patients.Results Mean age of patients and disease duration were 47.7 ± 10.5 and 17.0 ± 10.6 years, respectively. Twenty-one had pure HSP and SPG4 was the most frequent genotype. Mean Rankin and SPRS-BR scores were 2.2 ± 0.9 and 19.9 ± 9.9, respectively. Mean intra and inter-rater correlation coefficients of SPRS-BR scores were 0.951 and 0.934, whereas coefficients of variation were 11.5% (inter-rater) and 9.9% (intra-rater). Cronbach’s alpha for the whole SPRS-BR scale was 0.873.Conclusion SPRS-BR is a useful, reliable and valid clinical instrument.
Keywords: spastic paraplegia; hereditary; scales; tranlating